Civic Cultural Literacy Research Trend in Primary Schools: Tren Penelitian Literasi Budaya Kewarganegaraan di Sekolah Dasar - Syamsijulianto, Tri; Sapriya; Udin Syaefudin Sa’ud; Cepi Riyana; Tio Gusti Satria; Pranata, Alvira (Jurnal Elementaria Edukasia, 2024)
This study uses VOSviewer bibliometric analysis to chart the upward trajectory of civic cultural literacy research, particularly in primary schools. The goal of this study was to examine civic cultural literacy research trends using bibliometric analysis. Article data were collected using publication reference management systems and the Publish or Perish (PoP 8) database. Direct the search process by including the keywords "Cultural Literacy, Civic Literacy, Civic Cultural Literacy, and Elementary School" in the article's title and abstract. 1000. articles are utilized as samples and deemed appropriate. The literature included in the Google Scholar index between 2014 and 2024 provides research material. The statistics reveal that over time, the citations related to this paper are very few and even declined considerably. The statistics reveal that the number of citations linked with this work has decreased dramatically over time, as seen by the fact that there were 9004 citations in 2014. However, there will be just 410 citations at the end of 2023, and 28 citations by 2024. Based on density visualization data, the yellow color in the visualization suggests a dark direction, implying that this research is still extremely poorly done and provides a huge chance for future research on the phrase above